1979
DOI: 10.1007/bf00568202
|View full text |Cite
|
Sign up to set email alerts
|

The disposition of intravenous doxapram in man

Abstract: The pharmacokinetics of intravenous doxapram in healthy individuals is consistent with a three-compartment open model. Doxapram was administered by bolus injection (1.5 mg . kg-1) and by intravenous infusion (6.5 mg . kg-1 for 2 h) to 5 subjects on separate occasions. There was no significant difference in mean terminal plasma half-lives (355 and 448 min) or in mean total body clearances 5.9 and 5.6 ml . min-1 . kg-1) following i.v. bolus injection or infusion respectively. In 3 subjects plasma doxapram concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

1982
1982
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 12 publications
1
10
1
Order By: Relevance
“…We are unable to determine in the present study whether the differences between target and actual plasma levels resulted from differences in drug disposition, clearance, or nonlinear pharmacokinetic effects due to dosage scaling. Assuming a steady state plasma concentration was achieved before shivering occurred, the total plasma clearance calculated from our data was 12.9 ± 5 mL·kg -1 ·min -1 [range 5.8-21.5 mL·kg -1 ·min -1 ], a value larger than that reported by Clements et al (11). However, Jamali et al (24) found that 4 of 17 neonates had much greater clearance rates of doxapram (19.0-29.2 mL·kg -1 ·min -1 ) than the others.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…We are unable to determine in the present study whether the differences between target and actual plasma levels resulted from differences in drug disposition, clearance, or nonlinear pharmacokinetic effects due to dosage scaling. Assuming a steady state plasma concentration was achieved before shivering occurred, the total plasma clearance calculated from our data was 12.9 ± 5 mL·kg -1 ·min -1 [range 5.8-21.5 mL·kg -1 ·min -1 ], a value larger than that reported by Clements et al (11). However, Jamali et al (24) found that 4 of 17 neonates had much greater clearance rates of doxapram (19.0-29.2 mL·kg -1 ·min -1 ) than the others.…”
Section: Discussioncontrasting
confidence: 68%
“…Doxapram was infused using a modification of the simplified infusion regimen of Clements et al (11), which was stated to produce a constant plasma concentration of 2 μg/mL. In this case with an objective of 4 μg/mL, the infusion rates were doubled under the assumption of linear pharmacokinetics.…”
Section: Protocolmentioning
confidence: 99%
“…[21] have recently reported a mean elimination half-life of 9.9 ± 2.9 h for doxapram in apneic prematures. In the infants we studied the half-life of 6.6 ± 5.7 h was double that found in adult vol unteers [15]; however, the clearance of 420 ± 100 ml/kg/h was larger than in adults [15]. The large Vd of 4.1 ± 2.7 litre/kg in the babies studied, compared to adults [ 15], may explain this.…”
Section: Resultsmentioning
confidence: 60%
“…Because the prolonged half-life may significantly de lay reaching therapeutic levels, we also use a loading dose of 3 mg/kg given over 15 min as Clements et al [15] reported excessive re sponse with a rapid bolus in adults. This reg iment gave doxapram levels of 1.2-2.8 mg/1 within 2 h in 3 patients not included in this report.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation